ҮНДСЭН ХУУЛИЙН ДАРХЛАА - Д.Болд-Эрдэнэ (Politology, 2023)
Theterm "the privacy of the Constitution" is commonly used inconstitutional theory. In the most countries regulate in detail privacy of constitutional law. This makes it close to the legal possibility of arbitrary violence the Constitution. In this article we want to discuss this case in Mongolia.